Assessing changes in enriched maize flour formulations after extrusionby means of FTIR, XRD, and chemometric analysis - Cueto, Mario Alberto (2018)
Spectral analysis employing multivariate techniques was employed to differentiate plain maize flours from formulations containing maize with added milled chia or quinoa seeds for producing cereal breakfast extrudates. The physicochemical changes of the enriched formulations due to processing stages and formulation were evaluated by using FTIR and chemometric analysis, which allowed a rapid and non-destructive discrimination between sample processing and compositional aspects. Specific IR frequencies were selected which provided highest sample discrimination. Selected IR absorbance relationships at those specific wavenumbers were useful to track changes promoted by extrusion for carbohydrates, proteins, and lipids. The complexes between amylose and lipids, that takes place during extrusion, underwent distinctive changes as confirmed by XRD. The crystallinity loss, after extrusion (with an average value of 50%), shows evidence of amylose-lipid complexes formation of type Eh and Vh. Correlations between the textural behavior, composition, and selected FTIR indices were obtained.